Understanding Special Educators' Learning Opportunities in Collaborative Groups: The Role of Discourse. (May 2015) - Leko, Melinda M.; Kiely, Mary Theresa; Brownell, Mary T.; Osipova, Anna; Dingle, Mary P.; Mundy, Charlotte A.
The purpose of this study was to investigate the discourse patterns characterizing individual special education teachers as they participated in a collaborative professional development (PD) group, and how these individual discourse patterns influenced other group members' opportunities to learn about reading instruction for upper elementary students with disabilities. Videotaped cohort meetings and associated artifact data were collected during a 2-year period and analyzed using Gee's (2005) methods of discourse analysis. Findings indicate that teachers' individual discourse varied along the two dimensions: knowledge (integrated, implementation, and low) and inquiry (high and low). Teachers whose discourse conveyed both integrated knowledge and a proclivity for inquiry provided other group members with the most sophisticated learning opportunities related to PD content. Additional implications for future research and practice regarding collaborative learning groups as a method of PD are provided.